Ketepatan dimensi duplikat model dengan penggunaan agar-agar powder sebagai pengganti bahan cetak (Laporan Penelitian) - Erni Gultom; Bintang Simbolon; Linasari (Jurnal Kedokteran Gigi Terpadu, 2022)
This study aims to find alternative printing materials that are easy to apply and relatively cheap. As is known, the printed materials circulating so far are mostly imported, so it is difficult and expensive to get them. While in Indonesia, it is very easy and cheap to get gelatinous powder ( food ingredients) that can be used as an alternative material for printing materials. For this reason, several experiments were carried out by mixing existing alginate printing materials with gelatin powder in Indonesia with various compositions. The method used in this study is Laboratory experiments to get a mixture with setting time and dimensional stability close to ideal as an alternative printing material. The purpose of this study is to determine the Dimensional Stability between Alginate and Agar Powder.